Budaya Literasi Membaca Anak Autis SDLB - Indrariani, Eva Ardiana; Sophia, Th. Cicik (Mimbar Sekolah Dasar, 2018)
This study aims to describe the culture of reading literacy of autistic children in  elementary special schools (SDLB). Culture of Literacy in SLB adjusts to the conditions and situation of the children. In SDLB, there are various categories of children who have special abilities, one of whom is an autistic child. This study used a qualitative approach with observation and interview as its techniques for collecting the data. Data sources were obtained from autistic children and third-grade teachers of SDLB Talitakum Semarang. The results showed that the culture of reading literacy of the third-grade autistic children was carried out with several activities i.e. (1) listening to stories, narration, or texts, (2) reading with the teacher's guide, and (3) reading as they wish.